Case Report: Prostate Adenocarcinoma With Mucinous Features of Normal-Level Serum PSA, Atypical Imaging, Biopsy-Negative, and Peculiar Urethrocystoscopic Manifestation - Zhang, Yao; Shen, Hua; Liao, Kai; Wu, Weili; Li, Jiuming; Yu, Hongbo; Wu, Hongfei; Wang, Zengjun (Frontiers in Oncology, 2020)
Background: Mucinous tumors of the prostate are seen as rare morphological variants of prostate carcinoma. Misdiagnosis and missed diagnosis are frequent clinically, especially when the clinical performance appears atypical. Furthermore, there has not been reported about the urethrocystoscopic performance of mucinous adenocarcinoma growing into the prostatic urethra so far. Case Presentation: The current case report describes a 48-year old Asian male who was hospitalized because of intermittent gross hematuria for more than two months. The patient was diagnosed as prostatic space occupying lesions and an examination of needle biopsy was conducted on him, which did not indicate a definite malignancy. Transurethral plasma kinetic resection of the prostate (TUPKP) was performed for the patient, but the postoperative pathology revealed prostatic adenocarcinoma with mucinous features. Specifically, two cord-like neoplasms, extending to the bladder neck, were found through urethrocystoscopy in the prostatic urethra, both of which grew pedicles. The pedicles were situated on the right side of the parenchyma of the prostate. Finally, the patient underwent radical prostatectomy three weeks later. Conclusion: Here, we reported a case that prostatic adenocarcinoma with mucinous features was diagnosed after TUPKP. The patient had normal serum prostate-specific antigen levels with atypical images and negative biopsy result. This report lays stress on the vigilance of clinicians in prostate mucinous adenocarcinoma and makes a description of its peculiar urethrocystoscopic manifestation, typical imaging, and unique growth pattern for the first time.